Mental health of administrative employees and teachers at a professional and technological education institution (Research, Society and Development, 2024)
This article aims to describe the prevalence of stress, anxiety and depression in administrative staff and teachers of a federal education institute in the state of Espírito Santo, Brazil. It also aims to analyze sociodemographic factors associated with these mental health variables. To this end, a quantitative and cross-sectional study was developed with a sample of 62 education professionals, 32 teachers and 30 administrative employees. Participants answered a questionnaire with sociodemographic variables (professional career, ethnicity, age group, gender, and monthly family income) and the Depression, Anxiety, and Stress Scale. Descriptive and inferential statistics were analyzed with the aid of SPSS software, version 27.0. The results indicated a prevalence of 33.87% of moderate to extremely severe levels of stress, 29.03% of anxiety, and 37.10% of depression in the sample. Bivariate analyses demonstrated that there were no associations between the participants’ ethnicity and mental health variables. They also demonstrated that the groups most vulnerable to mental disorders were technical-administrative education professionals, younger people, women and employees with lower monthly family incomes. These results indicate the need to develop public educational policies aimed at protecting and promoting the mental health of education professionals and preventing illness, especially among the most vulnerable groups. The final considerations present the limitations of the study and provide suggestions for future research.